The physics of structure formation: theory and simulation; proceedings of an Internat. Symposium Tübingen, Fed. Rep. of Germany, October 27 - November 2, 1986 - Güttinger, Werner; Dangelmayr, Gerhard (Springer Series in Synergetics, 1987)
I Disordered Systems, Networks and Patterns -- Neural Networks - Achievements, Prospects, Difficulties -- Pattern Recognition in Nonlinear Neural Networks -- Formation of Ordered Structures in Quenching Experiments: Scaling Theory and Simulations -- Patterns in Random Boolean Nets -- The Structure of the Visual Field -- Patterns of Maximal Entropy -- II Structure Formation in Nonlinear Systems -- Patterns of Bifurcation from Spherically Symmetric States -- Structure Formation by Propagating Fronts -- Oscillatory Doubly Diffusive Convection: Theory and Experiment -- Pattern Selection in Anisotropic Systems -- Rayleigh Number Ramps Cause Moving Convection Patterns -- Interactions of Stationary Modes in Systems with Two and Three Spatial Degrees of Freedom -- The Basic (n,2n)-Fold of Steady Axisymmetric Taylor Vortex Flows -- III Interfacial Patterns -- Nonlinear Interactions of Interface Structures of Differing Wavelength in Directional Solidification -- Velocity Selection in Dendritic Growth -- Interfacial Pattern Formation: Dynamical Effects -- IV Diffusion Limited Aggregation and Fractals -- Role of Fluctuations in Fluid Mechanics and Dendritic Solidification -- A Stochastic Model for Arborescent and Dendritic Growth -- Electrodeposition: Pattern Formation and Fractal Growth -- Anisotropy and Fluctuation in Diffusion Limited Aggregation -- The Classes of Fractals -- Structural Characterization of Aluminum Hydroxide Aggregates by S.A.X.S.: Comparison Between Simulations of Fractal Structures and Experiments -- V Chaos and Turbulence -- Spatial Disorder in Extended Systems -- Nonlinear Gravity Waves and Resonant Forcing -- Transitions to Chaos in a Finite Macroscopic System: Direct Numerical Simulations Versus Normal Form Predictions -- Time-Dependent and Chaotic Behaviour in Systems with O(3)-Symmetry -- Selfsimilarity of Developed Turbulence -- VI Bifurcations and Symmetry -- Nonlinear Normal Modes of Symmetric Hamiltonian Systems -- The Ubiquitous Astroid -- On the Hopf Bifurcation with Broken O(2) Symmetry -- Generic Spontaneous Symmetry Breaking in SU(n) - Equivariant Bifurcation Problems -- Computer Algebraic Tools for Applications of Catastrophe Theory -- Computer Algebra Programs for Dynamical Systems Theory -- Index of Contributors